The Association Between Lysosomal Storage Disorder Genes and Parkinson’s Disease: A Large Cohort Study in Chinese Mainland Population - Yu-wen Zhao (Frontiers Media S.A., 2021)
Background: Recent years have witnessed an increasing number of studies indicating an essential role of the lysosomal dysfunction in Parkinson’s disease (PD) at the genetic, biochemical, and cellular pathway levels. In this study, we investigated the association between rare variants in lysosomal storage disorder (LSD) genes and Chinese mainland PD.Methods: We explored the association between rare variants of 69 LSD genes and PD in 3,879 patients and 2,931 controls from Parkinson’s Disease & Movement Disorders Multicenter Database and Collaborative Network in China (PD-MDCNC) using next-generation sequencing, which were analyzed by using the optimized sequence kernel association test.Results: We identified the significant burden of rare putative LSD gene variants in Chinese mainland patients with PD. This association was robust in familial or sporadic early-onset patients after excluding the GBA variants but not in sporadic late-onset patients. The burden analysis of variant sets in genes of LSD subgroups revealed a suggestive significant association between variant sets in genes of sphingolipidosis deficiency disorders and familial or sporadic early-onset patients. In contrast, variant sets in genes of sphingolipidoses, mucopolysaccharidoses, and post-translational modification defect disorders were suggestively associated with sporadic late-onset patients. Then, SMPD1 and other four novel genes (i.e., GUSB, CLN6, PPT1, and SCARB2) were suggestively associated with sporadic early-onset or familial patients, whereas GALNS and NAGA were suggestively associated with late-onset patients.Conclusion: Our findings supported the association between LSD genes and PD and revealed several novel risk genes in Chinese mainland patients with PD, which confirmed the importance of lysosomal mechanisms in PD pathogenesis. Moreover, we identified the genetic heterogeneity in early-onset and late-onset of patients with PD, which may provide valuable suggestions for the treatment.